Ritual 'Amoek' Melayu: Rekonstruksi atas Ritus-ritus Kekerasan di Indonesia - AAGN Ari Dwipayana (Jurnal Ilmu Sosial dan Ilmu Politik, 2001)
The display of violence is needed by the rulers who need to ensure that its power relationship is unchallenged. By using the same logic the ruled also having potential of expressing violence. Such an expressioni is called amoek.